THE CONTRIBUTION OF BRAIN DOMINANCE TO READING SKILL OF IELTS - Ismail Ismail; Herminus Efrando Pabur; Sukmawati Yasim; Umar Umar (SoCul: International Journal of Research in Social Cultural Issues, 2023)
A popular theory in neuroscience, brain dominance, has influenced on education since studying of human brain plays important role to improve quality of teaching and learning outcomes. The purpose of this study is to find out the significant correlation between brain hemispheric dominance and reading skill of IELTS, and to identify the significant difference among students at the same level who have different categories of brain dominance in reading skill of IELTS. Students’ score in reading of IELTS and categories of brain dominance in the basis of personal traits and cognitive styles from 114 students of three different universities at the context of EFL were correlated and analyzed in Pearson Chi-Square, Kruskall –Wallis, and Mann-Whitney. The findings show that there is significant correlation between two variables. Different categories of brain dominance influence on students’ reading skill of IELTS. Findings of this study support what the theorists of brain dominance claim that individuals who have different brain dominance tend to be different in doing specific tasks.